Peran Dewan Pengawas Syariah terhadap Kinerja Bank Pembangunan Daerah Jambi Syariah - Tri Wahyuda; Bambang Kurniawan; Khusnul Istiqomah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The Sharia Supervisory Board (DPS) has an important role in supervising and ensuring compliance by the Jambi Syariah Regional Development Bank (BPDSJ) with sharia principles. This research aims to identify the role of DPS on BPDSJ performance in the context of supervision of sharia aspects. The research method used is qualitative with a descriptive approach. Data was collected through in-depth interviews with DPS members, bank management and relevant regulators. The research results show that DPS plays a role in determining sharia policies, conducting sharia audits, and providing recommendations to improve bank performance in implementing sharia principles. In this context, DPS plays a key role in maintaining the integrity and credibility of BPDSJ in the eyes of the public and increasing customer trust in sharia banking services.